The rapid vertical handover for efficient IPv6 mobility support in heterogeneous wireless network - Abdullah, Radhwan Mohammed; Abdullah, Azizol; Abdul Hamid, Nor Asilah Wati; Othman, Mohamed; Subramaniam, Shamala (Springer, 2014)
The management techniques employed for Fast Mobile Internet Protocol version 6 (FMIPv6) and Media Independent Handover services between different wireless technologies are very important for completing the handover operations with the least possible delay. In the FMIPv6 technique, when a mobile node (MN) moves to another network, it needs to perform vertical handover (VHO) operations. These operations have a severe impact on the handover latency. In this article, we propose an enhanced network layer mechanism that is used to support fast handover for VHO. We introduce a new idea for the access router discovery method and propose a rapid VHO algorithm accordingly. Our proposal of a rapid VHO algorithm, a previous access router (pAR), rapidly provides a unique Ipv6 address instead of a new access router (nAR) for MNs. The binding updates to both the home agent and the correspondent node are performed from the pAR. We can observe from the results that by optimizing the network layer, the rapid VHO algorithm rapidly presents unique Ipv6 addresses for MNs with a minimum handover latency and packet loss even at high-speed movements. Finally, we presented an analytical model which shows that by enabling the access router discovery method and enhancing the network layer mechanism, an MN can perform fast handover processes with low handover latency compared with the FMIPv6 technique.